Reducing interethnic social distance among adolescents through participation in life-skills groups - Howe, E. (International Journal of Adolescent Medicine and Health, 1999)
Keywords: adolescence; adolescent; article; attitude; cognitive defect; coping behavior; counseling; dept.swk; ethnic group; female; group psychology; human; human experiment; male; peer-reviewed; problem solving; social behavior; social interaction; social psychology; social status; socialization

Self-help for grandmothers parenting again - Winston, Carole A (Journal of Social Distress and The Homeless, 1999)
Increasingly, grandmothers are parenting grandchildren in homes where parental presence is sporadic or nonexistent. A disproportionate percentage of African American grandparents fall in this category. The author reviews the literature on the African American grandmother in the context of the African American family and describes a practice model for service provision to those women who seek support as they “parent again.”
Keywords: African American; Empowerment model; Parenting grandparents; Support group; dept.swk